A design-time data-centric maturity model for assessing resilience in multi-party business processes. (December 2019) - Marrella, Andrea; Mecella, Massimo; Pernici, Barbara; Plebani, Pierluigi
Abstract: Nowadays, every business organization operates in ecosystems and cooperation is mandatory. If, on the one hand, this increases the opportunities for the involved organizations, on the other hand, every business partner is a potential source of failures with impacts on the entire ecosystem. To avoid that these failures, which are local to one of the organizations, would block the whole cooperation, resilience is a feature that multi-party business processes currently support at run-time, to cope with unplanned situations caused by those failures. In this work, we consider awareness of resilience in multi-party business processes during design-time, by focusing on the role of available – as an alternative to unreliable – data as a resource for increasing resiliency, as data exchange usually drives the cooperation among the parties. In fact, a proper analysis of involved data allows the process designer to identify (possible) failures, their impact, and thus improve the process model at the outset. A maturity model for resilience awareness is proposed, based on a modeling notation extending OMG CMMN — Case Management Model and Notation, and it is organized in different resiliency levels, which allow designers (i) to model at an increasing degree of detail how data and milestones should be defined in order to have resilient by-design process models and (ii) to quantify the distance between a process model and the complete achievement of a resiliency level. Highlights: A design-time maturity model for process models. A formal extension of OMG CMMN, enabling suitable data-driven extensions. A framework for classifying resiliency levels of CMMN process models. A complete step-by-step case study, showing all the peculiarities of the approach.